Phytoconstituents and pharmaco‐therapeutic benefits of pitaya: A wonder fruit. Issue 7 (7th May 2020) - Joshi, Monica; Prabhakar, Bala
Abstract: Dragon fruit has caught the attention of many researchers in the last few years because of its vast therapeutic potential. The fruit is enriched with several phytochemical constituents having tremendous pharmacological properties. It is traditionally used as a coloring agent. Some newly explored therapeutic applications include its use as an antioxidant, antimicrobial, antidiabetic, anticancer, and nutraceutical. The phytoconstituents can be extracted from flesh, peel, and seeds of the fruit. The fruit is known to be a rich source of betacyanin, vitamin C, and lycopene. The current review is focused on phytochemical constituents of dragon fruit along with its pharmacological activities. It also sheds light on the safety aspects of the fruit. The review will pave a path for researchers to study this marvel fruit further for societal benefit. Advanced research on dragon fruit will unleash many more therapeutic benefits and can give mechanistic insight about its activities. Practical applications: Phytoconstituents play a vital role in the treatment of various diseases and for the improvement of human health, in general. Dragon fruit is known to be having antioxidant, anti‐microbial, anti‐diabetic, anti‐cancer applications. The fruit can also be used as a nutraceutical (functional food). To grab all the benefits from this fruit, its phytoconstituents and pharmaco‐therapeutic aspect have to be thoroughly studied. This review can be very useful for researchers across different fields like botany, agriculture, pharmacy, etc., to bridge the gap for collaborative work on dragon fruit, which will help in finding solutions for many modern diseases. Abstract : All the parts of the dragon fruit, namely, flesh, peel and seeds are enriched with several phytoconstituents. The phytoconstituents of the dragon fruit are linked with therapeutic properties like antioxidant, antimicrobial, anti‐diabetic, anticancer, and nutraceutical. The review provides a framework for researchers across different fields to establish the mechanistic correlation between the phytoconstituents and therapeutic benefits of this wonder fruit.